Body Composition in Adolescents and Young Adults with Anorexia Nervosa: A Clinical Review - Tannir, Hana; Itani, Leila; Kreidieh, Dima; El Masri, Dana; Traboulsi, Samira; El Ghoch, Marwan (Current Rheumatology Reviews, 2020)
Background: Anorexia nervosa is a serious health condition characterized by a significant low body weight and alteration in body composition components. Aim: In the current paper, we aim to summarize the available literature concerning changes in body fat, lean, and bone masses, during anorexia nervosa and after complete weight restoration. Methods: Data were summarized using a narrative approach based on clinical expertise in the interpretation of the available evidence base in the literature. Results: The available data revealed three main findings. Firstly, anorexia nervosa causes a significant reduction in body fat mass, however it is completely restored after short-term weight normalization but with a central adiposity phenotype that does not seem to negatively influence treatment outcomes and appears to normalize after 1 year of normal weight maintenance. Secondly, anorexia nervosa causes a significant reduction in bone mineral density, but weight restoration is associated first (≈12 months) with stabilization of bone mineral density, followed by improvements (after ≈16 months); and finally, with complete normalization (after ≈30 months) after normal-weight maintenance. Thirdly, during anorexia nervosa loss of lean and skeletal body mass occurring in particular from the extremities rather than the central regions has been consistently reported, especially in patients with a Body Mass Index (BMI) ≤ 16.5 Kg/m2 however short-term weight restoration is associated with complete normalization. Conclusion: Anorexia nervosa adversely affects body composition, however this medical complication seems to be reversible through the main treatment strategy of body weight restoration followed by normal weight maintenance, and this should be openly discussed with patients.
Keywords: body composition